Improving the investment climate in Nigeria : issues and policy options - Muogbo, Chinonso Onyekachi; Kayar, Fahrettin (Universitetet i Nordland, 2012)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2012